The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1809-98232013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Análise da percepção de um grupo de idosos a respeito de seu handicap auditivo antes e após o uso do aparelho auditivo

Abstract: INTRODUÇÃO: A presbiacusia, ou perda auditiva causada pelo envelhecimento, pode gerar dificuldades comunicativas, psicológicas e sociais nos indivíduos idosos, com impactos profundos em sua vida social e familiar. OBJETIVO: Este estudo visou analisar a percepção de um grupo de idosos a respeito de seu handicap auditivo antes e após o uso do aparelho auditivo. MÉTODOS: Foi aplicado um questionário a 29 idosos oriundos de um hospital particular da cidade de Curitiba, PR. Neste estudo, os idosos responderam a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
(11 reference statements)
0
10
0
4
Order By: Relevance
“…[10][11][12] The psychological and social damage (participation restrictions) arising from hearing loss is described as a handicap. 13,14 The evaluation of the impact of hearing loss on emotional and social aspects can be accomplished through the application of self-assessment questionnaires. These instruments can be used to quantify the subjective and qualitative dimensions of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The psychological and social damage (participation restrictions) arising from hearing loss is described as a handicap. 13,14 The evaluation of the impact of hearing loss on emotional and social aspects can be accomplished through the application of self-assessment questionnaires. These instruments can be used to quantify the subjective and qualitative dimensions of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos idosos entrevistados não apresenta percepção do handicap auditivo. O impacto positivo do uso do AASI na vida social e na percepção do handicap do idoso foi relatado por GUARINELLO et al (2013), ao comprovarem que o uso da prótese diminuiu os efeitos da perda auditiva sobre a comunicação e as relações pessoais. Desta forma, evidencia-se a importância do uso do AASI, pois este dispositivo pode diminuir a percepção dos indivíduos sobre as limitações da vida social proporcionando qualidade de vida ao idoso.…”
Section: Resultsunclassified
“…Este fato pode ser explicado pelos benefícios efetivos, tanto sociais quanto emocionais, proporcionados pelo uso do aparelho de amplificação sonora individual por parte dos idosos que compõem a amostra desta pesquisa, pois a melhora na sensibilidade auditiva pode ter diminuído o grau de percepção do handicap. GUARINELLO et al (2013) analisaram a percepção do handicap auditivo em um grupo de idosos com perda auditiva predominantemente do tipo neurossensorial antes e após um ano de uso do aparelho auditivo, tempo médio de adaptação do paciente. Concluíram que o uso da prótese diminuiu os efeitos da perda auditiva sobre a comunicação, pois houve diminuição da percepção do handicap auditivo e das queixas relacionadas às limitações no convívio social.…”
Section: Tabela 4 -Grau Deunclassified
“…As regards the performance in the HHIE-S, results showed statistically significant differences, not only in the experimental group, but also in the control group (eight participants), qualitatively superior to the processing tests, which indicates that the use of the HA contributed to a better hearing, reducing considerably the restriction of participation. A research applied the same questionnaire to 29 elderly, before the use of the hearing aid and after one year of use, resulting in a significant reduction in the restriction of participation after the use of hearing aid, in the group studied (24) . Another study, also similar, demonstrated that the elderly showed reduction in the self-perception of the restrictions of participation after the use of the hearing aid, attributing this improvement to the adaptation and the use of hearing aids (25) .…”
Section: Discussionmentioning
confidence: 99%